2014
DOI: 10.1002/2014ja020410
|View full text |Cite
|
Sign up to set email alerts
|

DEMETER observations of bursty MF emissions and their relation to ground‐level auroral MF burst

Abstract: Citation:Broughton, M. C., J. LaBelle, and M. Parrot (2014) Similar to MF burst, the bursty MF waves observed by DEMETER have broadband, impulsive frequency structure covering 1.5-3.0 MHz, amplitudes of 50-100 μV/m, an overall occurrence rate of ∼0.76% with higher occurrence during active times, and strong correlation with auroral hiss. The magnetic local time distribution of the MF waves observed by DEMETER shows peak occurrence rate near 18 MLT, somewhat earlier than the equivalent peak in the occurrence rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In summary, we establish that among the 25 events with peaks above ground level, median MFB source heights range from 139 to 296 km with a median of 208 km. These sources appear to be on the topside of the density profile, with the profile peaking in the E region, qualitatively consistent with the mechanism of generation of MFB from mode conversion of Langmuir waves excited at a range of altitudes, hence a range of plasma frequencies, on the topside ionosphere (Broughton et al, 2015;LaBelle, 2011). Our findings present the possibility of a new method of estimating polar cap density based on these measurements.…”
Section: 1029/2020ja028166supporting
confidence: 80%
See 1 more Smart Citation
“…In summary, we establish that among the 25 events with peaks above ground level, median MFB source heights range from 139 to 296 km with a median of 208 km. These sources appear to be on the topside of the density profile, with the profile peaking in the E region, qualitatively consistent with the mechanism of generation of MFB from mode conversion of Langmuir waves excited at a range of altitudes, hence a range of plasma frequencies, on the topside ionosphere (Broughton et al, 2015;LaBelle, 2011). Our findings present the possibility of a new method of estimating polar cap density based on these measurements.…”
Section: 1029/2020ja028166supporting
confidence: 80%
“…However, further modeling efforts are needed to confirm whether this model is quantitatively consistent with the source altitudes found in Figure 7, since the applications of the model shown in Figure 3 of LaBelle (2011) are at somewhat higher altitudes. Propagation to ground level should be possible as long as the MFB frequency exceeds the maximum L cutoff frequency below the source, as explained by LaBelle (2011) and Broughton et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…A finite k ⊥ could cause a mode conversion between the downward propagating Langmuir/Z mode wave to an upward propagating LO mode wave, which would further attenuate the wave energy density of the downward propagating Langmuir/Z mode wave. This type of mode conversion has been observed in warm plasma simulations [ Kim et al , , , ] and could be the source of the bursty MF waves observed by Detection of Electro‐Magnetic Emissions Transmitted from Earthquake Regions at approximately 700 km [ Broughton et al , ]. In the context of the mode conversion of upper hybrid waves, Schleyer et al [] simulated mode conversion for a large range of parameters and found that for ionospheric conditions, the angle‐averaged energy mode conversion efficiency from the upper hybrid mode to the one of the electromagnetic modes ranged from ∼10 −10 to 10 −3 .…”
Section: Discussionmentioning
confidence: 83%
“…In addition, recent studies have shown ground‐level detection of auroral kilometric radiation below 800 kHz [ LaBelle and Anderson , ; LaBelle et al ., ] and the discovery of natural radio emissions between f ce and 2 f ce (1.3–2.2 MHz) [ Broughton et al ., ]. Satellite‐based detections of auroral radio emissions with frequencies greater than ~ 1 MHz have also been reported by several studies [ James et al ., ; Oya et al ., ; Bale , ; Shinbori et al ., ; Sato et al ., ; Broughton et al ., ], which were termed terrestrial hectometric radiation (THR) by Oya et al . [].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more broadband, bursty emissions like ground‐level MFB were found from satellite measurement by Broughton et al . [] and were referred to as “bursty MF waves” (peak δf / f ~ 0.5). They argued that the satellite‐level bursty MF waves might be the same phenomena as ground‐level MFB and also reported a single event where ground‐level detection of MFB was almost concurrent with bursty MF waves detected by Detection of Electro‐Magnetic Emissions Transmitted from Earthquake Regions, a polar orbiting satellite (670 km altitude, 1000 km southeast of the ground station).…”
Section: Introductionmentioning
confidence: 99%